PENDUGAAN TINGGI TANAMAN KAYU PUTIH (Melaleuca Cajuputi) UNTUK EVALUASI PERTUMBUHAN TANAMAN REHABILITASI DAS - Fandi Oktiawan; Yudi F. Arifin; Raihani Wahdah; Erma Agusliani (EnviroScienteae, 2022)
Watershed Rehabilitation activities are one of the efforts in carrying out soil and water conservation. Evaluation of plant growth Watershed rehabilitation needs to be carried out to determine the success of these activities. In a case study at the Gunung Batu block location, it was found that there was a positive and strong correlation between the variable height dimension increase and crown diameter increase in Kayu Putih (Melaleuca cajuputi) plants. The regression equation was built using the dimensional variables of Total Plant Height as a result of ground sampling and the diameter of the crown as a result of orthophoto drone interpretation. By using 4 regression equation models, it was concluded that the best coefficient of determination was generated from the exponential regression model with a value of = 0.96 with the equation y = 0.3016e1.3573x which was built using a height class of 20 cm. The accuracy test was carried out to see how far the standard deviation of the model was. Estimation of the height of 23 Kayu Putih (Melaleuca cajuputi) plants with a height range of 1.2 to 3.5 meters was carried out using 4 regression equation models, where the data were plant data that were not used in building 4 models. The best standard deviation value produced is 0.11 meters which is obtained from the range of plant heights from 1.2 to 1.8 meters using the exponential regression model equation.